Will terrorists go nuclear? - Jenkins, Brian Michael (Prometheus Books, 2008)
Introduction -- A shiver of terror -- Growing concern -- The first imaginings -- Motives -- Self-imposed constraints -- Nuclear coercion: just hoaxes? -- Designing the threat -- Black markets -- A small cup of Italian coffee -- Lebed's lost luggage -- Visions of mass destruction -- The "new terrorism" -- From a balance of terror to a world unhinged -- An age of alarms -- America the anxious -- The first terrorist nuclear power -- Is deterrence dead? -- A self-sustaining fission of fear -- A choice of reactions -- A brilliant yellow light -- Reflections on the shadows of doom -- Countering our own fear -- Footnotes